Efektifitas Mempopulerkan Tempat Wisata Di Tangerang Melalui Media Sosial Youtube - Catur Putro Utomo; Wesly Friendman Hutahaean (UNIVERSITAS RAHARJA, 2018)
Social media youtube currently has been known many people , it is all because of the more people who uses social media youtube for uploaded or watched the video yotube , so that in this study we make various went on places can be taken for sites that people can spend timed close , traveled , recreation , or just plain walk leisurely to refresh mind for people who live in the Tangerang and surroundingDue to lack of information is complete and accurate about video place tourism in Tangerang, usually only a picture and the written, and if there are video, the video derived from sources that different so it confused the community to receive the information, hopefully with the channel youtube this, all information regarding what tourism in Tangerang will find it easier to find, because it contains information on all places tourism in Tangerang to be information clearly, and everyone definitely does not will feel confusion again and laborious in search of information tourist destinations in Tangerang.